EFFECTS OF SOYBEAN MEALSUBSTITUTION WITHFERMENTED LEUCENA(Leucaena leucocephala)LEAVES MEAL IN THE DIETS ON THE GROWTH ANDFEED EFFICIENCY OF GOURAMY(Osphronemusgouramy Lac.) - Mahdi Arif Siregar; Indra Suharman; Adelina Adelina (Berkala Perikanan Terubuk, 2016)
The purpose of this research was to know efects of soybean meal subtitution with leucena leaves fermented trial in the diets on the growth, feed efficiency , feed digestibility and protein retention of gouramy.Five experimental diets was formulated to contain 0,10,20,30, and 40% fermented leucena leaves meal and 100,90,80,70, and 60% soybean meal (P0,P1,P2,P3,P4, respectively). Completely randomized design (CRD) was used in this experiment.The result of this research showed that a diet containing 30% fermented leucena leaves meal and 70% soybean meal (P3) support a good specific growth rate (2,13%), feed efficiency (34,82%), feed digestibility (64,91%), and protein retention (30,37%). It is concluded that 30% soybean meal can be substituted with fermented leucena leaves meal in the diets for gouramy.